2014
DOI: 10.5268/iw-4.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Geoengineering in lakes: welcome attraction or fatal distraction?

Abstract: The use of geoengineering techniques for phosphorus management offers the promise of greater and quicker chemical and ecological recovery. It can be attractive when used with other restoration measures but should not be considered a panacea. The range of materials being proposed for use as well as the in-lake processes targeted for manipulation continues to grow. With increasing political imperatives to meet regulatory goals for water quality, we recommend a coordinated approach to the scientific understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…Source-oriented measures principally targeting the phosphorus inflow and internal loading remain essential in reducing eutrophication [32]. However, in situations where source-oriented measures are not easy achievable, cost-effective end-of-pipe solutions might be an alternative, but these should have proven efficacy in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Source-oriented measures principally targeting the phosphorus inflow and internal loading remain essential in reducing eutrophication [32]. However, in situations where source-oriented measures are not easy achievable, cost-effective end-of-pipe solutions might be an alternative, but these should have proven efficacy in situ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the demand of society and the governments for good water quality is urgent. Some countries have set compulsory goals for water quality improvement within short period of time and large amount of funds were attached (Mackay et al, 2014). In-lake measures of geo-engineering may be useful to meet this urgent need, although long term ecological safety must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Since the natural restoration processes are far slower than the time scale of these management targets, ecological safe/ effective and environmentally friendly in-lake technologies for quick control of internal nutrient loads are required. Recently, geoengineering in lakes has caused much interest for eutrophication control, which can offer the promise of rapid effects (Mackay et al, 2014;Spears et al, 2013). Some conventional geo-engineering materials, such as aluminum-/iron-salts and solid-phase P sorbents (aluminum, iron and lanthanum modified soils/clays etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The frequent outbreak of cyanobacterial blooms in eutrophic waters is a global issue, posing serious threats to aquatic ecosystem and human health Liu and Le, 2015;Lu et al, 2013;Wang et al, 2013c). Modified soils (MSs) have triggered great interest as geo-engineering materials for cyanobacterial bloom control in recent years (Lürling and van Oosterhout, 2013;Mackay et al, 2014;Spears et al, 2014;Tian et al, 2014). Although many studies on algal removal using MSs have been reported (Li and Pan, 2013;Pan et al, 2011a;Shi et al, 2015;Zou et al, 2005), little is known about its potential impacts on the receiving waters.…”
Section: Introductionmentioning
confidence: 99%